Assessing Farmers’ Perception on Climate Change and its Consequences: A Case Study in the Baba Mountain Valleys of Bamyan, Afghanistan - Hasani, Mustafa; Shrestha, Rajendra Prasad (European Journal of Applied Sciences, 2024)
Climate change poses significant challenges in the vulnerable regions like Afghanistan, where agriculture is main source of peoples’ livelihoods. This study examines the farmers’ perspectives and their experiential insights into changing climate indicators and its impacts on agriculture. Through a combination of quantitative and qualitative data collection methods, including household surveys, focus group discussions, historical timeline calendars, crop calendars, and key informant interviews, the study identifies changes in climate indicators as perceived by farmers. The study’s findings highlight a range of changes in climate indicators. The farmers have experienced decreasing snowfall in winter and annual rainfall in spring and summer, consequently the intense frequent drought and water shortages for agriculture and rangelands in the upper and lower part of the valleys. The temperatures in winter and summer have increased and led to earlier snow melting, earlier blooming, flowering, and greening of the plants. Both positive and negative impacts, brought by the shift in climate indicators, have presented new cultivation opportunities but also led to droughts, water shortages and reduced productivity. These findings can be valuable inputs for effective ecosystem and community-based adaptation strategies at local level, guiding for a resilient planning and policies for addressing current and future climate impacts on agriculture.